High-stability Ga ion doped sintered calcium aluminate / Ni composite catalyst as well as preparation method and application thereof
The distribution of nickel particles is improved by Ga ion doping, and a high-stability calcium aluminate/Ni composite catalyst is prepared, which solves the problem of inactivation caused by nickel agglomeration and significantly improves catalytic activity and stability.
Patent Information
- Application Number
- CN202510091279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
Existing nickel-based calcium aluminate catalysts are prone to inactivate due to nickel agglomeration under high temperature conditions, resulting in insufficient catalytic stability.
The distribution of nickel particles in the support is improved by Ga ion doping, and the migration resistance of nickel is enhanced, and a high-stability, Ga ion doped sintered calcium aluminate/Ni composite catalyst is prepared.
Inactivation caused by nickel agglomeration is effectively avoided, and the catalytic activity and high-temperature catalytic stability of the composite catalyst are significantly improved.
Smart Images

Figure CN119819308A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic material preparation and application, and in particular to a high-stability Ga-ion-doped sintered calcium aluminate / Ni composite catalyst and a preparation method and application thereof. Background Art
[0002] The ways to produce hydrogen include natural gas reforming, water electrolysis, photoelectrolysis, and biological processes. At present, large-scale production of hydrogen is mainly based on the chemical reaction of fossil fuels and the electrolysis of water. Both of these have been fully developed at the industrial level, and there is almost no room for major technological breakthroughs and cost reduction in the main processes. However, the energy consumed by decomposing water through electrolysis is huge, and the proportion of hydrogen produced by electrolysis of water is only about 5%. The process of producing hydrogen using fossil fuels as raw materials still dominates. Methane has the highest hydrogen-to-carbon ratio of all hydrocarbons and is considered to be the most suitable raw material for hydrogen production. Methane steam reforming is the oldest and most mature method in the methane reforming process.
[0003] Methane steam reforming is the main process for producing hydrogen, and the usual reaction conditions are high temperature (1023K-1223K) and high pressure (14-20atm). In addition to providing sufficient specific surface area and suitable pore structure for the catalyst, a good catalyst carrier must also have sufficient mechanical strength to cope with high steam partial pressure and air flow scouring. Porous calcium aluminate ceramics are suitable industrial catalyst carriers based on their good chemical and thermal stability. However, after long-term use, nickel-based calcium aluminate catalysts will inevitably be deactivated due to nickel agglomeration. Therefore, it is necessary to study a composite catalyst with high stability. Summary of the invention
[0004] The purpose of the present invention is to provide a highly stable, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst and its preparation method and application. The present invention can improve the distribution of nickel particles in the carrier through Ga-ion doping, enhance the migration resistance of nickel, effectively avoid the deactivation caused by nickel agglomeration, and improve the high-temperature catalytic stability of the composite catalyst.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing a highly stable, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, the specific steps of which are as follows:
[0007] S1. Preparation of calcium aluminate carrier:
[0008] Pre-calcining Al(OH)3 and CaCO3 to obtain calcium aluminate powder, mixing the calcium aluminate powder with Ga2O3, and performing secondary calcination to obtain a calcium aluminate carrier;
[0009] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0010] The calcium aluminate carrier prepared in step S1 is immersed in a saturated nickel nitrate hexahydrate solution, dried, and then subjected to high-temperature decomposition and oxidation, and then reduced with H2 to obtain a calcium aluminate / Ni composite catalyst.
[0011] Furthermore, in step S1, the mass ratio of Al(OH)3 to CaCO3 is 1:0.2-0.3.
[0012] Furthermore, in step S1, the temperature range of the pre-calcination and the secondary calcination is 1300-1400°C, preferably 1350°C.
[0013] The heating rate of the pre-calcination and secondary calcination is 4-6°C / min, preferably 5°C / min.
[0014] The holding time of the pre-calcination and the secondary calcination is 100 to 200 minutes, preferably 150 minutes.
[0015] Furthermore, in step S1, the specific preparation method of the calcium aluminate carrier is as follows:
[0016] S1-1, pre-calcining Al(OH)3 and CaCO3 to obtain calcium aluminate powder;
[0017] S1-2, mixing the calcium aluminate powder prepared in step S1-1 with Ga2O3, adding alcohol, and ball milling to obtain a ball mill material after the mixture is evenly mixed;
[0018] S1-3, drying the ball mill prepared in step S1-2, pressing it into a round sheet-shaped body, and calcining it at high temperature to obtain a calcium aluminate carrier.
[0019] Furthermore, in step S1-2, the content of Ga2O3 in the calcium aluminate powder is 0.5wt% to 2.0wt%.
[0020] As a preferred technical solution, the doping amount of Ga2O3 in the calcium aluminate powder includes 0.5wt%, 1wt%, 1.5wt% and 2.0wt%.
[0021] Furthermore, in step S1-2, the mass ratio of the calcium aluminate powder to the alcohol is 1:1.
[0022] As a preferred technical solution, in step S1-2, the ball milling time is 12 hours.
[0023] As a preferred technical solution, in step S1-3, the drying temperature is 120°C and the drying time is 4 hours.
[0024] As a preferred technical solution, in step S1-3, the pressing pressure is 1t / m 2 .
[0025] Furthermore, in step S2, the mass ratio of the calcium aluminate carrier to the saturated nickel nitrate hexahydrate solution is 1:8-12, preferably 1:10.
[0026] As a preferred technical solution, the temperature of the saturated nickel nitrate hexahydrate solution is 60°C, and the Ni loading is 8-12wt% of the mass of the calcium aluminate carrier, preferably 10wt%.
[0027] Furthermore, in step S2, the oxidation temperature range is 500-600°C, preferably 520°C.
[0028] The heating rate of the oxidation is 2-4°C / min, preferably 3°C / min.
[0029] The oxidation holding time is 100 to 200 minutes, preferably 150 minutes;
[0030] The temperature range of H2 reduction is 600-800°C, preferably 700°C.
[0031] The heating rate of H2 reduction is 4-6°C / min, preferably 5°C / min.
[0032] The reaction time of the H2 reduction is 1 to 2 hours, preferably 2 hours.
[0033] Furthermore, in step S2, the specific preparation method of the calcium aluminate / Ni composite catalyst is as follows:
[0034] S2-1, immersing the calcium aluminate carrier prepared in step S1 in a saturated nickel nitrate hexahydrate solution, placing it into an alumina crucible after drying, and performing high-temperature decomposition and oxidation in a high-temperature muffle furnace;
[0035] S2-2, reducing the carrier oxidized in step S2-1 with H2 in a reactor to obtain a calcium aluminate / Ni composite catalyst.
[0036] The present invention also provides a highly stable, Ga-ion-doped, sintered calcium aluminate / Ni composite catalyst. The calcium aluminate / Ni composite catalyst is gray-brown in color as a whole, has a complete particle structure, and nickel nanoparticles are dispersed on the surface of the calcium aluminate carrier.
[0037] In addition, the present invention also provides an application of a highly stable, Ga-ion-doped, sintered calcium aluminate / Ni composite catalyst, wherein the calcium aluminate / Ni composite catalyst is used in a methane steam reforming process.
[0038] Furthermore, the process steps are:
[0039] The calcium aluminate / Ni composite catalyst is mixed with quartz sand, CH4 and H2O are introduced, and methane steam reforming is carried out at 700-900°C.
[0040] Furthermore, in the above, the mass ratio of the calcium aluminate / Ni composite catalyst to quartz sand is 1:5-6.
[0041] As a preferred technical solution, the flow rate of CH4 is 267 ml / min, and the flow rate of H2O is 0.194 ml / min.
[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0043] 1. The present invention can increase the proportion of larger pores in the carrier through Ga ion doping, increase gas diffusion channels, improve the distribution of nickel particles in the carrier, enhance the migration resistance of nickel, effectively avoid deactivation caused by nickel agglomeration, and significantly improve the catalytic activity and catalytic stability of the composite catalyst.
[0044] 2. The present invention utilizes Ga2O3 to dope and modify the calcium aluminate catalyst carrier, optimizes the pore size distribution of the carrier, increases the strength of the carrier, improves the distribution of nickel particles in the carrier, enhances the migration resistance of nickel, and improves the high-temperature catalytic stability of the composite catalyst.
[0045] 3. The calcium aluminate / Ni composite catalyst of the present invention has a significant porous layered structure and more stable performance. Its methane conversion rate shows high stability after long-term catalytic testing, and its physical structure is more completely preserved after the catalytic experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Example 3;
[0047] Figure 2 Schematic diagram of the catalytic activity of the calcium aluminate / Ni composite catalyst prepared in Example 3 and Comparative Example 1;
[0048] Figure 3 Schematic diagram of the catalytic stability of the calcium aluminate / Ni composite catalyst prepared in Example 3 and Comparative Example 1;
[0049] Figure 4 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Example 3 after the experiment;
[0050] Figure 5 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Comparative Example 1 after the experiment. DETAILED DESCRIPTION
[0051] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0052] The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0053] In conjunction with the accompanying drawings, some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.
[0054] Example 1
[0055] This embodiment provides a method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, and the specific steps are as follows:
[0056] S1. Preparation of calcium aluminate carrier:
[0057] S1-1, 83g of Al(OH)3 and 17g of CaCO3 were mixed, the temperature was raised to 1350°C at 5°C / min, and the heat preservation time was 150min to obtain calcium aluminate powder;
[0058] S1-2. Add 0.5 wt% of Ga2O3 to the calcium aluminate powder prepared in step S1-1, put it in a ball mill, set the ball mill speed to 40 r / min, add 100 g of alcohol, and obtain the ball milled material after ball milling for 12 hours.
[0059] S1-3, drying the ball mill prepared in step S1-2 in an oven at 120°C for 4 hours, taking 1.2 g of the dried ball mill, and heating it at 1 t / m 2 The pellets were pressed into 12 mm diameter pellets at a pressure of 1.5°C, heated to 1350°C at a rate of 5°C / min in a muffle furnace, and kept at this temperature for 150 min to obtain a calcium aluminate carrier.
[0060] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0061] S2-1, placing the disc-shaped calcium aluminate carrier prepared in step S1 into a saturated nickel nitrate hexahydrate solution at 60°C to ensure that the Ni loading is 10wt%, drying and then placing in a muffle furnace for oxidation at an oxidation temperature of 520°C, a heating rate of 3°C / min, and a holding time of 150min;
[0062] S2-2. Grind the oxidized disc-shaped carrier in step S2-1 in a reactor, pass it through a 10-30 mesh sieve, place it in a reduction reactor, seal it, and continuously introduce H2 for 1 hour to ensure that there is no air remaining in the furnace. Raise the temperature to 700°C at a rate of 5°C / min, continue the reaction for 2 hours, reduce NiO to elemental Ni, and obtain a calcium aluminate / Ni composite catalyst.
[0063] Example 2
[0064] This embodiment provides a method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, and the specific steps are as follows:
[0065] S1. Preparation of calcium aluminate carrier:
[0066] S1-1, 83g of Al(OH)3 and 17g of CaCO3 were mixed, the temperature was raised to 1350°C at 5°C / min, and the heat preservation time was 150min to obtain calcium aluminate powder;
[0067] S1-2. Add 1 wt% of Ga2O3 to the calcium aluminate powder prepared in step S1-1, put it in a ball mill, set the ball mill speed to 40 r / min, add 100 g of alcohol, and obtain the ball milled material after ball milling for 12 hours.
[0068] S1-3, drying the ball mill prepared in step S1-2 in an oven at 120°C for 4 hours, taking 1.2 g of the dried ball mill, and heating it at 1 t / m 2 The pellets were pressed into 12 mm diameter pellets at a pressure of 1.5°C, heated to 1350°C at a rate of 5°C / min in a muffle furnace, and kept at this temperature for 150 min to obtain a calcium aluminate carrier.
[0069] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0070] S2-1, placing the disc-shaped calcium aluminate carrier prepared in step S1 into a saturated nickel nitrate hexahydrate solution at 60°C to ensure that the Ni loading is 10wt%, drying and then placing in a muffle furnace for oxidation at an oxidation temperature of 520°C, a heating rate of 3°C / min, and a holding time of 150min;
[0071] S2-2. Grind the oxidized disc-shaped carrier in step S2-1 in a reactor, pass it through a 10-30 mesh sieve, place it in a reduction reactor, seal it, and continuously introduce H2 for 1 hour to ensure that there is no air remaining in the furnace. Raise the temperature to 700°C at a rate of 5°C / min, continue the reaction for 2 hours, reduce NiO to elemental Ni, and obtain a calcium aluminate / Ni composite catalyst.
[0072] Example 3
[0073] This embodiment provides a method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, and the specific steps are as follows:
[0074] S1. Preparation of calcium aluminate carrier:
[0075] S1-1, 83g of Al(OH)3 and 17g of CaCO3 were mixed, the temperature was raised to 1350°C at 5°C / min, and the heat preservation time was 150min to obtain calcium aluminate powder;
[0076] S1-2. Add 1.5 wt% of Ga2O3 to the calcium aluminate powder prepared in step S1-1, put it in a ball mill, set the ball mill speed to 40 r / min, add 100 g of alcohol, and obtain the ball milled material after ball milling for 12 hours.
[0077] S1-3, drying the ball mill prepared in step S1-2 in an oven at 120°C for 4 hours, taking 1.2 g of the dried ball mill, and heating it at 1 t / m 2 The pellets were pressed into 12 mm diameter pellets at a pressure of 1.5°C, heated to 1350°C at a rate of 5°C / min in a muffle furnace, and kept at this temperature for 150 min to obtain a calcium aluminate carrier.
[0078] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0079] S2-1, placing the disc-shaped calcium aluminate carrier prepared in step S1 into a saturated nickel nitrate hexahydrate solution at 60°C to ensure that the Ni loading is 10wt%, drying and then placing in a muffle furnace for oxidation at an oxidation temperature of 520°C, a heating rate of 3°C / min, and a holding time of 150min;
[0080] S2-2. Grind the oxidized disc-shaped carrier in step S2-1 in a reactor, pass it through a 10-30 mesh sieve, place it in a reduction reactor, seal it, and continuously introduce H2 for 1 hour to ensure that there is no air remaining in the furnace. Raise the temperature to 700°C at a rate of 5°C / min, continue the reaction for 2 hours, reduce NiO to elemental Ni, and obtain a calcium aluminate / Ni composite catalyst.
[0081] Example 4
[0082] This embodiment provides a method for preparing a calcium aluminate / Ni composite catalyst, and the specific steps are as follows:
[0083] S1. Preparation of calcium aluminate carrier:
[0084] S1-1, 83g of Al(OH)3 and 17g of CaCO3 were mixed, the temperature was raised to 1350°C at 5°C / min, and the heat preservation time was 150min to obtain calcium aluminate powder;
[0085] S1-2. Add 2.0 wt% of Ga2O3 to the calcium aluminate powder prepared in step S1-1, put it in a ball mill, set the ball mill speed to 40 r / min, add 100 g of alcohol, and obtain the ball milled material after ball milling for 12 hours.
[0086] S1-3, drying the ball mill prepared in step S1-2 in an oven at 120°C for 4 hours, taking 1.2 g of the dried ball mill, and heating it at 1 t / m 2 The pellets were pressed into 12 mm diameter pellets at a pressure of 1.5°C, heated to 1350°C at a rate of 5°C / min in a muffle furnace, and kept at this temperature for 150 min to obtain a calcium aluminate carrier.
[0087] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0088] S2-1, placing the disc-shaped calcium aluminate carrier prepared in step S1 into a saturated nickel nitrate hexahydrate solution at 60°C to ensure that the Ni loading is 10wt%, drying and then placing in a muffle furnace for oxidation at an oxidation temperature of 520°C, a heating rate of 3°C / min, and a holding time of 150min;
[0089] S2-2. Grind the oxidized disc-shaped carrier in step S2-1 in a reactor, pass it through a 10-30 mesh sieve, place it in a reduction reactor, seal it, and continuously introduce H2 for 1 hour to ensure that there is no air remaining in the furnace. Raise the temperature to 700°C at a rate of 5°C / min, continue the reaction for 2 hours, reduce NiO to elemental Ni, and obtain a calcium aluminate / Ni composite catalyst.
[0090] Comparative Example 1
[0091] This embodiment provides a method for preparing a calcium aluminate / Ni composite catalyst, and the specific steps are as follows:
[0092] S1. Preparation of calcium aluminate carrier:
[0093] S1-1, 83g of Al(OH)3 and 17g of CaCO3 were mixed, the temperature was raised to 1350°C at 5°C / min, and the heat preservation time was 150min to obtain calcium aluminate powder;
[0094] S1-2. The calcium aluminate powder prepared in step S1-1 is placed in a ball mill, the ball mill speed is set to 40 r / min, 100 g of alcohol is added, and the ball milled material is obtained after ball milling for 12 hours.
[0095] S1-3, drying the ball mill prepared in step S1-2 in an oven at 120°C for 4 hours, taking 1.2 g of the dried ball mill, and heating it at 1 t / m 2The pellets were pressed into 12 mm diameter pellets at a pressure of 1.5°C, heated to 1350°C at a rate of 5°C / min in a muffle furnace, and kept at this temperature for 150 min to obtain a calcium aluminate carrier.
[0096] S2. Preparation of calcium aluminate / Ni composite catalyst:
[0097] S2-1, placing the disc-shaped calcium aluminate carrier prepared in step S1 into a saturated nickel nitrate hexahydrate solution at 60°C to ensure that the Ni loading is 10wt%, drying and then placing in a muffle furnace for oxidation at an oxidation temperature of 520°C, a heating rate of 3°C / min, and a holding time of 150min;
[0098] S2-2. Grind the oxidized disc-shaped carrier in step S2-1 in a reactor, pass it through a 10-30 mesh sieve, place it in a reduction reactor, seal it, and continuously introduce H2 for 1 hour to ensure that there is no air remaining in the furnace. Raise the temperature to 700°C at a rate of 5°C / min, continue the reaction for 2 hours, reduce NiO to elemental Ni, and obtain a calcium aluminate / Ni composite catalyst.
[0099] Methane steam reforming experiment
[0100] The calcium aluminate / Ni composite catalysts prepared in Example 3 and Comparative Example 1 were subjected to a methane steam reforming experiment, and the specific process is as follows:
[0101] 0.8g of calcium aluminate / Ni composite catalyst was evenly mixed with 4.25g of quartz sand, and transferred to the catalyst experimental device for the experiment. CH4 and H2O were introduced, the methane flow rate was controlled at 267ml / min, the water pump flow rate was controlled at 0.194ml / min, and the reaction temperature was 800℃. After the experiment was carried out for 6 hours, the sample was removed after cooling and optical photos were taken.
[0102] Performance Characterization
[0103] See also Figure 1 , Figure 1 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Example 3. The particle structure is complete, the calcium aluminate / Ni composite catalyst is gray-brown as a whole, the particle structure is complete, and the nickel nanoparticles are well dispersed on the surface of the calcium aluminate carrier.
[0104] See also Figure 2 , Figure 2 Schematic diagram of the catalytic activity (CH4 conversion rate) of the calcium aluminate / Ni composite catalyst prepared in Example 3 and Comparative Example 1. Figure 2 It can be seen that within the temperature range of 550°C to 800°C, the calcium aluminate / Ni composite catalyst prepared in Example 3 has higher catalytic activity.
[0105] See also Figure 3, Figure 3 Schematic diagram of the catalytic stability of the calcium aluminate / Ni composite catalyst prepared in Example 3 and Comparative Example 1. Figure 3 It can be seen that after 6 hours of methane steam reforming test, the catalytic efficiency of the calcium aluminate / Ni composite catalyst prepared in Example 3 did not decay significantly, while the catalytic efficiency of the calcium aluminate / Ni composite catalyst prepared in Comparative Example 1 decayed significantly.
[0106] See also Figure 4 and Figure 5 , Figure 4 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Example 3; Figure 5 This is an optical photograph of the calcium aluminate / Ni composite catalyst prepared in Comparative Example 1 after the experiment. Figure 4 and Figure 5 It can be seen that the physical structure of the calcium aluminate / Ni composite catalyst in Example 3 is more intact, indicating that it is more suitable for harsh working conditions.
[0107] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a highly stable, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, characterized in that: The specific steps are as follows: S1. Preparation of calcium aluminate carrier: Pre-calcining Al(OH)3 and CaCO3 to obtain calcium aluminate powder, mixing the calcium aluminate powder with Ga2O3, and performing secondary calcination to obtain a calcium aluminate carrier; S2. Preparation of calcium aluminate / Ni composite catalyst: The calcium aluminate carrier prepared in step S1 is immersed in a saturated nickel nitrate hexahydrate solution, dried, and then subjected to high-temperature decomposition and oxidation, and then reduced with H2 to obtain a calcium aluminate / Ni composite catalyst.
2. The method for preparing a highly stable, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 1, characterized in that: In step S1, the mass ratio of Al(OH)3 to CaCO3 is 1:0.2-0.3; The temperature range of the pre-calcination and the secondary calcination is 1300-1400°C. The heating rate of the pre-sintering and secondary sintering is 4-6°C / min. The holding time of the pre-sintering and secondary sintering is 100 to 200 minutes.
3. The method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 1, characterized in that: In step S1, the specific preparation method of the calcium aluminate carrier is as follows: S1-1, pre-calcining Al(OH)3 and CaCO3 to obtain calcium aluminate powder; S1-2, mixing the calcium aluminate powder prepared in step S1-1 with Ga2O3, adding alcohol, and ball milling to obtain a ball mill material after the mixture is evenly mixed; S1-3, drying the ball mill prepared in step S1-2, pressing it into a round sheet-shaped body, and calcining it at high temperature to obtain a calcium aluminate carrier.
4. The method for preparing a highly stable, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 3, characterized in that: In step S1-2, the content of Ga2O3 in the calcium aluminate powder is 0.5wt% to 2.0wt%; In step S1-2, the mass ratio of the calcium aluminate powder to the alcohol is 1:
1.
5. The method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 1, characterized in that: In step S2, the mass ratio of the calcium aluminate carrier to the saturated nickel nitrate hexahydrate solution is 1:8-12, and the loading amount of Ni is 8-12wt% of the mass of the calcium aluminate carrier; The oxidation temperature range is 500-600°C. The heating rate of the oxidation is 2-4°C / min, The oxidation holding time is 100 to 200 minutes; The temperature range of H2 reduction is 600-800°C. The heating rate of H2 reduction is 4-6°C / min, The reaction time of the H2 reduction is 1 to 2 hours.
6. The method for preparing a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 1, characterized in that: In step S2, the specific preparation method of the calcium aluminate / Ni composite catalyst is as follows: S2-1, immersing the calcium aluminate carrier prepared in step S1 in a saturated nickel nitrate hexahydrate solution, placing it into an alumina crucible after drying, and performing high-temperature decomposition and oxidation in a high-temperature muffle furnace; S2-2, reducing the carrier oxidized in step S2-1 with H2 in a reactor to obtain a calcium aluminate / Ni composite catalyst.
7. A high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, characterized in that: The calcium aluminate / Ni composite catalyst obtained by the preparation method as described in any one of claims 1 to 6 is gray-brown as a whole, has a complete particle structure, and nickel nanoparticles are dispersed on the surface of the calcium aluminate carrier.
8. Application of a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst, characterized in that: The calcium aluminate / Ni composite catalyst obtained by the preparation method as described in any one of claims 1 to 6 is used in a methane steam reforming process.
9. The use of a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 8, characterized in that: The process steps are: The calcium aluminate / Ni composite catalyst is mixed with quartz sand, CH4 and H2O are introduced, and methane steam reforming is carried out at 700-900°C.
10. The use of a high-stability, Ga-ion-doped sintered calcium aluminate / Ni composite catalyst according to claim 9, characterized in that: The mass ratio of the calcium aluminate / Ni composite catalyst to quartz sand is 1:5-6.